CULTURAL LANDSCAPE AND BUILT HERITAGE IN PORT CITIES OF THE RECÔNCAVO BAIANO: A STUDY FOR PRESERVATION - Silva, Luís Cláudio Requião da (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
This article deals with the urban dimension of the heritage and is located within the Historical Urban Geography with the emergency of a regional spatial narrative from the analysis of the cultural landscape of seven port historic cities of the Reconcavo Baiano, region which is located in the vicinity of All Saints Bay, state of Bahia, Brazil.